Holocene sea-level change in the New Zealand archipelago and the geomorphic evolution of a holocene coastal plain incised-valley system : the lower Manawatu valley, North Island, New Zealand : a thesis presented in partial fulfilment of the requirements for the degree of Doctor of Philosophy in Geography at Massey University, Palmerston North, New Zealand - Clement, Alastair John Hopton (Massey University, 2011)
The full body of work relating to Holocene sea-level histories in the New Zealand region has been integrated and critically analysed to provide context for the construction of detailed, local-scale Holocene sea-level curves for regions within the New Zealand archipelago. These local-scale sea-level reconstructions in turn provide context for an investigation of the stratigraphic and geomorphic evolution of the Manawatu coastal plain incised-valley system during the Holocene. The state of knowledge of sea-level fluctuations in the New Zealand region during the Holocene is revealed to be poor. Holocene sea-level histories are fragmented and unreliable, with sea-level reconstructions produced for the whole of the New Zealand masking local-scale trends in Holocene sea-level fluctuations. Local-scale Holocene sea-level curves produced for regions within the New Zealand archipelago show a north-south trend in sea-level fluctuations. In the Auckland-Northland region present mean sea-level (PMSL) was attained c. 7,700 cal. yr BP. Approximately 7,500 cal. yr BP PMSL was attained in the southwest North Island. PMSL was attained in Pegasus Bay c. 7,100 - 6,600 cal. yr BP, and in East Otago c. 6,900 cal. yr BP. It is also possible to discern a north-south lag in the timing of sea-level fluctuations following the attainment of PMSL between the southwest coast of the North Island and the East Otago peninsula. The degree to which the north-south lag in the timing of the attainment of PMSL is a manifest response to external driving forces is not yet clear as the local-scale sea-level histories are highly variable, quite contradictory, and appear to be responding inconsistently to different external drivers. Vibracores and water well logs have been used to reconstruct the sedimentary infill of the lower Manawatu River valley, North Island, New Zealand, in response to Holocene sea-level change and the influx of sediment from the bordering axial ranges. Cross-sections across the incised-valley system have identified: the lowstand incision of the Manawatu River c. 22 -18 ka, and associated fluvial terraces buried at depth beneath the Holocene valley fill; the extent of the Holocene estuary which occupied the lower valley at the culmination of the Holocene marine transgression (c. 7,500 cal. yr BP); the sedimentary succession which filled the valley associated with the Holocene sea-level highstand; and late Holocene to recent coastal progradation of 5 - 6 km. A 3D model of the sub-surface stratigraphy of the lower valley was constructed from the borehole data and cross sections. Digital elevation models were also constructed for key palaeo-surfaces within the valley's Holocene sedimentary fill. Holocene sea-level fluctuations in the valley were reconstructed from radiocarbon dated estuarine bivalves recovered from vibracores. These radiocarbon dates also record subsidence of the valley due to a combination of sediment compaction, post-glacial water and sediment loading, the evolution of the Wanganui Basin, and neotectonics. Information from all sources was collated and used for the construction of palaeogeographic maps and a series of conceptual models of the evolution of the lower valley.
Keywords: Sea level; Manawatu; New Zealand; Holocene stratigraphic geology